(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
One of the main economic and social wealth of Uzbekistan is its people. Although policymaker pay the special attention at the gender equality in almost every aspect of our lives, we still have gender bias in our labor market. The current study empirically investigated the relationship between female labor force participation and economic prosperity of the country. How women participation may increase productivity of the country is clearly explained in this article. Also it includes the challenges women are facing in today’s modern life and how this issue may affect to the overall well-being of the economic activities in one particular country (Uzbekistan). Furthermore, this article gives some solutions for empowering female participation in economic activities.